Seleksi Segregan Gandum (Triticum aestivum L.) pada Dataran Tinggi - Wardani, Sri; Wirnas, Desta; Wahyu, Yudiwanti (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2015)
Pedigree selection is a method of selection used in segregating populations which takes the expertise of breeders in achieving the desired goal. This method is implemented on the early generations with a high degree of segregation and is generally performed on highly heritable traits. The purpose of this research was to study the performance of F3 generation segregants and to estimate the genetic parameters to be used for identification and selection of wheat segregants under optimum environmental condition. The research was carried out at the experiment field of  Research Institute for Ornamental Crops, in Cipanas from May to September 2012. Genetic material used were 58 F3 family and six check varieties, namely  Dewata, Selayar, Oasis, Rabe, Basribey, and HP 1744. The experiment used an augmented design. Results of analysis of variance showed that the family effect was significant for days to flowering, days to harvest, percentage of empty florets, number of grains per panicle, grain weight per panicle, number of seeds per plant and seed weight per plant. High heritability estimates were  found in days to flowering, days to harvest, seed filling period, percentage of empty florets, number of grains per panicle, grain weight per panicle, number of seeds per plant, and seed weight per plant. These characters are suitable for yield improvement of tropical highland wheat due to its high heritability values. The mean value of F3 generation changes subsequent to selection either based on grain weight per plant, or based on  number of productive tillers,  number of grain per panicle, and grain weight per plant. Keywords: selection criteria, segregation, tropical, yield